Non-Pharmacological Self-Management Strategies for Chemotherapy-Induced Peripheral Neuropathy in People with Advanced Cancer: A Systematic Review and Meta-Analysis - Crichton, Megan; Yates, Patsy M.; Agbejule, Oluwaseyifunmi Andi; Spooner, Amy; Chan, Raymond J.; Hart, Nicolas H. (Nutrients, 2022)
Non-pharmacological self-management interventions for chemotherapy-induced peripheral neurotherapy (CIPN) are of clinical interest; however, no systematic review has synthesized the evidence for their use in people with advanced cancer. Five databases were searched from inception to February 2022 for randomized controlled trials assessing the effect of non-pharmacological self-management interventions in people with advanced cancer on the incidence and severity of CIPN symptoms and related outcomes compared to any control condition. Data were pooled with meta-analysis. Quality of evidence was appraised using the Revised Cochrane Risk of Bias Tool for Randomized Trials (RoB2), with data synthesized narratively. Grading of Recommendations, Assessment, Development and Evaluations (GRADE) was applied to assess the certainty of the evidence. Thirteen studies were included, which had a high (69%) or unclear (31%) risk of bias. Greatest confidence was found for physical exercise decreasing CIPN severity (SMD: −0.89, 95% CI: −1.37 to −0.41; p = 0.0003; I2 = 0%; n = 2 studies, n = 76 participants; GRADE level: moderate) and increasing physical function (SMD: 0.51, 95% CI: 0.02 to 1.00; p = 0.04; I2 = 42%; n = 3 studies, n = 120; GRADE level: moderate). One study per intervention provided preliminary evidence for the positive effects of glutamine supplementation, an Omega-3 PUFA-enriched drink, and education for symptom self-management via a mobile phone game on CIPN symptoms and related outcomes (GRADE: very low). No serious adverse events were reported. The strongest evidence with the most certainty was found for physical exercise as a safe and viable adjuvant to chemotherapy treatment for the prevention and management of CIPN and related physical function in people with advanced cancer. However, the confidence in the evidence to inform conclusions was mostly very low to moderate. Future well-powered and appropriately designed interventions for clinical trials using validated outcome measures and clearly defined populations and strategies are warranted.